Local agro-industrial by-products offer feasible options to supplement breeding rams in mixed farming systems of Ethiopia - Belayneh, Tesfa; Asmare, Bimrew; Alkhtib, Ashraf; Wamatu, Jane (Elsevier, 2025)
The study assessed the supplemental effect of flushing Menz breeding rams with local agro-industrial by-products on their reproductive performance and semen quality. It recommends the use of wheat bran-based supplementation strategies to enhance the reproductive performance, semen quality, and the potential of Menz rams to serve ewes.